The Influence of Environmental Concern, Green Perceived Knowledge, and Green Trust on Green Purchase Intention - Chairy, Chairy; Alam, Meilisa Eka Nur (Jurnal Manajemen, 2019)
Global warming and environmental damage are some of the important current issues, which lead to the implementation of environmentally-friendly style of living. This study aims to identify the influence of environmental concern, green perceived knowledge, and green trust on green purchase intention. The population of this research was people who live in Jabodetabek. This study used online questionnaire and got responses from 300 respondents. The data were analyzed using SPSS version 22. The independent variables were environmental concern, green perceived knowledge, and green trust. The dependent variable was green purchase intention. This study concludes that there were positive and significant influences of environmental concern, green perceived knowledge and green trust on green purchase intention. The result of this study may be useful for the government to provide information on environmentally-friendly products, and also to provide recommendation for marketers in deciding on what products to produce.